Inflation without a Central Bank: The Role of Oil and Fiscal Shocks in Ecuador - Camacho-Villagomez, Freddy Ronalde (International Journal of Energy Economics and Policy, 2025)
This paper analyzes the inflationary effects of public spending and oil revenues in Ecuador, a small dollarized and oil-exporting economy. Using a structural vector autoregression (SVAR) model identified through institutional restrictions, we disentangle the dynamic impact of government investment, government consumption, and oil revenues on inflation. Our findings reveal that both oil revenues and government investment have statistically significant and persistent effects on the price level, whereas government consumption shows no significant impact. These results suggest that fiscal policy, particularly public investment financed by oil revenues, is a key transmission channel of external shocks to inflation in the absence of monetary policy autonomy. Robustness checks confirm the validity of our conclusions across alternative specifications.